Small firms in Portugal : a selective survey of stylized facts, economic analysis, and policy implications - Cabral, Luís M.B. (2018)
I survey a number of stylized facts pertaining to the dynamics of firm entry, growth, and exit in competitive industries. I focus particularly on data for Portugal, although I also consider, for comparison purposes, data from other countries. I then present a series of theoretical models that attempt to explain the stylized facts and evaluate the welfare impact of market distortions. Finally, I derive a number of policy implications, all centered around the notion of economic mobility.